Practical Catalytic Cleavage of C(sp3)−C(sp3) Bonds in Amines. (1st July 2019) - Li, Wu; Liu, Weiping; Leonard, David K.; Rabeah, Jabor; Junge, Kathrin; Brückner, Angelika; Beller, Matthias
Abstract: The selective cleavage of thermodynamically stable C(sp 3 )−C(sp 3 ) single bonds is rare compared to their ubiquitous formation. Herein, we describe a general methodology for such transformations using homogeneous copper‐based catalysts in the presence of air. The utility of this novel methodology is demonstrated for Cα −Cβ bond scission in >70 amines with excellent functional group tolerance. This transformation establishes tertiary amines as a general synthon for amides and provides valuable possibilities for their scalable functionalization in, for example, natural products and bioactive molecules. Abstract : Spalten mit Luft : C(sp 3 )‐C(sp 3 )‐Einfachbindungen in Aminen können mit Kupfer‐Katalysatoren in Gegenwart von Luft gespalten werden. Der Nutzen dieser neuartigen Methode wird anhand der Cα −Cβ ‐Bindungsspaltung in >70 Aminen mit vielfältigen funktionellen Gruppen demonstriert.